Strategy for Preserving the Culture Existence of Bali-Hindu In the Midst of Majority Cultural in Praya Lombok - Widana, I Nyoman Murba; Juliaaningsih P, Eka M. (Jurnal Penelitian Agama Hindu, 2023)
This study aims to conduct a study related to the strategies implemented by the Bali-Hindu community in maintaining the cultural existence amidst the majority culture implemented by the Sasak people in Praya city, central Lombok. This research was designed in a qualitative interpretive manner in order to find answers to the formulation of the problems posed. Based on the results of this study, four contestation arenas were found which were part of the strategy to maintain Balinese cultural identity in responding to the vortex of the majority culture. First, improving the quality of education among the younger generation of Hindus. Second, strengthening cultural awareness through non-formal and informal education systems. Third, planting religious values through religious ritual activities. Fourth, acculturation of Balinese culture with Sasak culture. Fifth, strengthening the economic system of Hindus.